Incidental Detection of Renal Cell Carcinoma is an Independent Prognostic Marker: Results of a Long-Term, Whole Population Study. - Palsdottir, Helga Bjork; Hardarson, Sverrir; Petursdottir, Vigdis; Jonsson, Armann; Jonsson, Eirikur; Sigurdsson, Martin Ingi; Einarsson, Gudmundur Vikar; Gudbjartsson, Tomas (Journal of Urology, 2012)
The true effect of incidental detection on the survival of patients with renal cell carcinoma has been debated. We used centralized databases in Iceland to study prognostic factors of survival, focusing on the effect of incidental detection. This retrospective study included all living patients diagnosed with renal cell carcinoma in Iceland from 1971 to 2005. Hospital charts and histology were reviewed. Incidentally diagnosed renal cell carcinomas were compared to symptomatic tumors and prognostic factors were evaluated using Cox multivariate analysis. Of the 910 patients 254 (27.9%) were diagnosed incidentally, most often by abdominal ultrasound (29.5%) or computerized tomography (28.3%). The incidental detection rate increased from 11.1% in 1971 through 1975 to 39.2% in 2001 through 2005 (p <0.001). During the same period the incidence increased significantly in males but in females only during the last 5 study years. Mortality remained unchanged for each gender. Incidentally detected tumors were an average of 2.6 cm smaller and diagnosed at lower stage and lower grade than symptomatic tumors. Age and histology were similar in each group. TNM stage was by far the strongest independent prognostic factor of survival but age, calendar year of diagnosis and ESR were also significant. After correcting for confounders patients with symptomatic renal cell carcinoma had worse survival than those diagnosed incidentally. With increased incidence and unchanged mortality the survival of patients with renal cell carcinoma has improved. This is mainly related to a steep increase in incidental detection. Incidental detection affects survival favorably and to a greater extent than can be explained by lower stage compared to the survival of patients diagnosed with symptoms.